2017
DOI: 10.1111/jpm.12356
|View full text |Cite
|
Sign up to set email alerts
|

Care planning: a neoliberal three card trick

Abstract: Introduction The three card game, sometimes called find the queen, is a classic confidence trick, typically taking place on an impromptu table top, set up on pavement or street corner. The tricksters usually operate in teams, pulling in punters and 'losing' games with their fellows to persuade prospective speculators the game is winnable. For our titular purposes the three card trick serves as a metaphor for broader deceits. We are concerned with how well-meaning mental health nurses can enter into a set of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…The noted burden of record keeping and how this serves to keep skilled staff away from service users is not a new observation. This has been subject to previous inquiry and critical commentary that challenges some of the absurdities of writing about people without them or basing risk management upon absentee narratives (Coffey et al, ; McKeown, Wright, & Mercer, ). Our study adds an appreciation of how such tendencies towards privileging record keeping over direct care are bound up with staffing pressures and are inseparable from concerns regarding coercive practices and attempts to minimize them.…”
Section: Discussionmentioning
confidence: 99%
“…The noted burden of record keeping and how this serves to keep skilled staff away from service users is not a new observation. This has been subject to previous inquiry and critical commentary that challenges some of the absurdities of writing about people without them or basing risk management upon absentee narratives (Coffey et al, ; McKeown, Wright, & Mercer, ). Our study adds an appreciation of how such tendencies towards privileging record keeping over direct care are bound up with staffing pressures and are inseparable from concerns regarding coercive practices and attempts to minimize them.…”
Section: Discussionmentioning
confidence: 99%
“…As has been found elsewhere, strategic targets for care coordination and excessive administrative demands risk obscuring the work which really needs to be done, including engaging in the making and maintaining of sustained, collaborative, relationships [78]. In some critiques, the pressure to get paper (and computer) work done means that mental health care planning and coordination amounts to little more than a ‘three card trick’ which promises much but which, perversely, increases the distance between those who use and those who provide services [79]. In addition, as this and other studies have shown [80], faced with few colleagues to whom onwards referral might be made care coordinators can find themselves under pressure to expand the range of tasks they carry out.…”
Section: Discussionmentioning
confidence: 99%
“…McKeown, Wright and Mercer (2017) stress that 'them and us' cultures contribute to poor patient experiences in alienating environments, which further feeds a notion that overly coercive approaches from staff still remain. In order to build effective relationships, it is often necessary for professionals to relinquish some of their power (Warne & McAndrew, 2007).…”
mentioning
confidence: 99%
“…This distance that nurses are seeking, is almost the opposite of what is required in service user involvement in nursing processes, therefore a close proximity to service users. McKeown et al, (2017) stress that nurses are deceiving themselves if they try to justify excessive time needed for office paperwork at the expense of direct care. These apparently rational practices in which nurses engage, including copious documentation and risk assessments, recommended in policy documents, seemingly motivated by ideals about care, actually function to destroy the very essence of what it might mean to be a caring professional worker.…”
mentioning
confidence: 99%
See 1 more Smart Citation